Association Between Autoimmune Diseases and Spontaneous Cervicocranial Arterial Dissection - Li, Hao; Song, Pu; Yang, Wei; Yang, Le; Diao, Shanshan; Huang, Shicun; Wang, Yiqing; Xu, Xingshun; Yang, Yi (Frontiers in Immunology, 2022)
A series of biopsies and reports showed autoimmune diseases might be involved in the process of local inflammation related to spontaneous cervicocranial arterial dissection (SCCAD) occurrence. This retrospective case-control study examined the association between SCCADs and autoimmune diseases in patients and control subjects from 2014 to 2020. SCCAD patients and age/sex-matched control subjects were recruited and clinical data were collected. SCCAD was confirmed by digital subtraction angiography or high-resolution magnetic resonance imaging. The study included 215 SCCAD patients and 430 control subjects. Totally, 135 (62.8%) of the 215 cases were found SCCAD in the anterior circulation, 26 (12.0%) patients involved multiple vessels. Autoimmune disease occurred in 27 (12.6%) cases with SCCAD and 4 (0.9%) control subjects (p<0.001). A conditional multivariable logistic regression model was used to calculate the odds ratio for SCCAD among patients with a history of autoimmune disease, adjusting for hypertension, diabetes, hyperlipidemia, and smoking. After adjustment, autoimmune diseases were associated with SCCAD (p<0.001). After sub-analysis by a similar modeling strategy, significant associations were still observed in different subgroups, such as female group and male group as well as intramural hematoma (IMH) group and Non-IHM group. The association of SCCAD with autoimmune disease suggested that autoimmune mechanisms may be involved in some etiologies of SCCAD.